2022
DOI: 10.3389/fnbeh.2022.835444
|View full text |Cite
|
Sign up to set email alerts
|

Role of Environment and Experimenter in Reproducibility of Behavioral Studies With Laboratory Mice

Abstract: Behavioral phenotyping of mice has received a great deal of attention during the past three decades. However, there is still a pressing need to understand the variability caused by environmental and biological factors, human interference, and poorly standardized experimental protocols. The inconsistency of results is often attributed to the inter-individual difference between the experimenters and environmental conditions. The present work aims to dissect the combined influence of the experimenter and the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 93 publications
2
10
0
Order By: Relevance
“…A subsequent detailed analysis of this study revealed that the most salient difference between the laboratories might have been introduced by the experimenters 216 . The role of the experimenter effect has been further addressed and confirmed by other studies 217‐221 . Thus, a change in the experimenter(s) is likely to induce variability with behavioral assays in the same laboratory as well.…”
Section: Interlaboratory Variability With Behavioral Assays Used To C...supporting
confidence: 53%
See 1 more Smart Citation
“…A subsequent detailed analysis of this study revealed that the most salient difference between the laboratories might have been introduced by the experimenters 216 . The role of the experimenter effect has been further addressed and confirmed by other studies 217‐221 . Thus, a change in the experimenter(s) is likely to induce variability with behavioral assays in the same laboratory as well.…”
Section: Interlaboratory Variability With Behavioral Assays Used To C...supporting
confidence: 53%
“…216 The role of the experimenter effect has been further addressed and confirmed by other studies. [217][218][219][220][221] Thus, a change in the experimenter(s) is likely to induce variability with behavioral assays in the same laboratory as well. As a consequence, interlaboratory and within-laboratory variability with behavioral assays used to characterize neurobehavioral comorbidities in animal models cannot be avoided and should be considered when evaluating preclinical data such as discussed in this review.…”
Section: Variability With Behavioral Assays Used To Characterize Neur...mentioning
confidence: 99%
“…This holds specifically for mice. For one, an anxiety-inducing experimenter effect is always present (Nigri et al, 2022 ), unless the mice climb on the hand of the scientist to undergo testing willingly. The second reason is that systems such as Phenotyper ® or IntelliCage ® permit monitoring behavior over days or weeks, and free humans for other tasks.…”
Section: Concluding Perspectivesmentioning
confidence: 99%
“…One naturally occurring source of variation is the different experimenters themselves. However, the latest literature indicates that this is less of an issue, particularly if all involved parties are well trained [38,39]. To assess replicability of results across centers, a low number of centers already is sufficient.…”
Section: Protocols Standardization and Systematic Heterogenizationmentioning
confidence: 99%